1987
DOI: 10.1210/jcem-65-5-1014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Thyrotropin-Releasing Hormone (TRH) and TRH-Binding Sites in Human Nonsecreting Pituitary Adenomas

Abstract: Immunoreactive TRH (IR-TRH) and TRH-binding sites were sought in nonsecreting pituitary adenomas. [3H]TRH bound specifically to cellular membranes from 11 of 12 such adenomas studied, with a dissociation constant (Kd) of 50 +/- 5 (+/- SEM) nmol/L and a maximum number of binding sites of 76 +/- 16 fmol/mg membrane protein (range, 32-229 fmol/mg protein). IR-TRH was detected in all 8 of the tumors in which it was sought. The identity of the IR-TRH was verified by high pressure liquid chromatography. The tumor IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
5
14
0
Order By: Relevance
“…Highperformance liquid chromatography showed only one peak of immunoreactive material that eluted at the same position than synthetic 3H-TRH. The concentrations of immunoreactive TRH were in the same range as those obtained in nonsecreting adenomas and normal human pituitary [20].…”
Section: Trh Content O F Adenomatous Tissuesupporting
confidence: 71%
See 1 more Smart Citation
“…Highperformance liquid chromatography showed only one peak of immunoreactive material that eluted at the same position than synthetic 3H-TRH. The concentrations of immunoreactive TRH were in the same range as those obtained in nonsecreting adenomas and normal human pituitary [20].…”
Section: Trh Content O F Adenomatous Tissuesupporting
confidence: 71%
“…However, other authors have shown that SRIH receptors, although not numerous, could be present in nonsecreting adenomas. This proba bly explains the possible therapeutical effect of SRIH analogues in such cases [19], In a study focused on nonsecreting adenomas com pletely devoid of immunoreactive cells, we found spe cific TRH receptors in nearly all these adenomas [20]. The mean IQ of TRH-binding sites was similar to that found in PRL-and GH-secreting adenomas and in nor mal human pituitary.…”
Section: Receptor Studies In Nonsecreting Pituitary Adenomassupporting
confidence: 70%
“…PAM activity is expressed in all pituitary hormone-producing cells of the AP, a finding consistent with the presence of a multitude of regulatory peptides, many of which are amidated, in the pituitary gland (16,37,38). To investigate whether TRH acts in a paracrine fashion within cultured AP cells, we chose Dis as a highly specific tool to reduce the formation of bioactive TRH, which we previously established to be expressed in this system (11,12,15,16,28).…”
Section: Discussionmentioning
confidence: 78%
“…Reverse transcription was performed by incubating 1 mg total RNA with 1 ml of PowerScript reverse transcriptase (Clontech, USA) and 1 ml of 0.5 mg/ml oligo(dT) [12][13][14][15][16][17][18] primer (Life Technologies, USA) at 42°C for 70 minutes in 20 ml reaction buffer. RT products were diluted ten times with 10 mM Tricine-KOH (pH 9.2)/0.1 mM EDTA, and stored at -20°C until used for PCR.…”
Section: Histological Studiesmentioning
confidence: 99%